2010
DOI: 10.1007/s00586-010-1660-y
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the vertebral bodies and the intervertebral discs in lumbar segments adjacent to spondylolysis and spondylolisthesis: pilot study

Abstract: The objective is to evaluate the geometric parameters of vertebral bodies and intervertebral discs in spinal segments adjacent to spondylolysis and spondylolisthesis. This pilot cross-sectional study was an ancillary project to the Framingham Heart Study. The presence of spondylolysis and spondylolisthesis as well as measurements of spinal geometry were identified on CT imaging of 188 individuals. Spinal geometry measurements included lordosis angle, wedging of each lumbar vertebra and intervertebral disc. Las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 23 publications
0
21
1
1
Order By: Relevance
“…Disc degeneration was therefore aggravated by lumbosacral kyphosis. Been et al 28 studied the geometry of the vertebral bodies and intervertebral discs in patients with spondylolisthesis. They reported that in isthmic spondylolysis, when the vertebra started to slide forward the compensating mechanism of the lumbar spine was to increase the lumbar lordosis by increasing the wedging of the intervertebral disc above the slipped vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…Disc degeneration was therefore aggravated by lumbosacral kyphosis. Been et al 28 studied the geometry of the vertebral bodies and intervertebral discs in patients with spondylolisthesis. They reported that in isthmic spondylolysis, when the vertebra started to slide forward the compensating mechanism of the lumbar spine was to increase the lumbar lordosis by increasing the wedging of the intervertebral disc above the slipped vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, there was no difference of IFD at the L3, L4, and L5 level between spondylolytic and unaffected individuals. The most recent article about spondylolysis demonstrated that spinal morphology of individuals with L5 spondylolysis without listhesis is similar to that of individuals with normal lower spinal segments in the context of total lordotic angle, vertebral body wedging, and intervertebral disc wedging but did not address on IFD as major geometrical variable (Been et al, 2011). Masharawi et al reported some association between spondylolysis and the architecture of lumbar articular facets and interfacet region (Masharawi et al,2007a).…”
Section: Discussionmentioning
confidence: 99%
“…On lateral radiographs, we measured lumbar angle, vertebral body wedging, intervertebral disc wedging, sacral slope and pelvic incidence ( Fig. 1; variables defined in previous studies; Vialle et al 2005;Been et al 2011Been et al , 2010O'Brien et al 2004;De Carvalho et al 2010). Lumbar angle (LA) is a way to assess LL and was defined as the Cobb angle between the L1 cranial endplate and S1 cranial endplate.…”
Section: Angular Measurementsmentioning
confidence: 99%